CD39 identifies a microenvironment-specific anti-inflammatory CD8+ T-cell population in atherosclerotic lesions. (June 2019) - van Duijn, Janine; van Elsas, Marit; Benne, Naomi; Depuydt, Marie; Wezel, Anouk; Smeets, Harm; Bot, Ilze; Jiskoot, Wim; Kuiper, Johan; Slütter, Bram
Abstract: Background and aims: CD8 + T-cells have been attributed both atherogenic and atheroprotective properties, but analysis of CD8 + T-cells has mostly been restricted to the circulation and secondary lymphoid organs. The atherosclerotic lesion, however, is a complex microenvironment containing a plethora of inflammatory signals, which may affect CD8 + T-cell activation. Here, we address how this environment affects the functionality of CD8 + T-cells. Methods and results: We compared the cytokine production of CD8 + T-cells derived from spleens and enzymatically digested aortas of apoE −/− mice with advanced atherosclerosis by flow cytometry. Aortic CD8 + T-cells produced decreased amounts of IFN-γ and TNF-α compared to their systemic counterparts. The observed dysfunctional phenotype of the lesion-derived CD8 + T-cells was not associated with classical exhaustion markers, but with increased expression of the ectonucleotidase CD39. Indeed, pharmacological inhibition of CD39 in apoE −/− mice partly restored cytokine production by CD8 + T-cells. Using a bone-marrow transplantation approach, we show that TCR signaling is required to induce CD39 expression on CD8 + T-cells in atherosclerotic lesions. Importantly, analysis of human endarterectomy samples showed a strong microenvironment specific upregulation of CD39 on CD8 + T-cells in the plaques of human patients compared to matched blood samples. Conclusions: Our results suggest that the continuous TCR signaling in the atherosclerotic environment in the vessel wall induces an immune regulatory CD8 + T-cell phenotype that is associated with decreased cytokine production through increased CD39 expression in both a murine atherosclerotic model and in atherosclerosis patients. This provides a new understanding of immune regulation by CD8 + T-cells in atherosclerosis. Graphical abstract: Image 1 Highlights: CD8 + T-cells in atherosclerotic lesions show impaired IFN-γ and TNF-α production, associated with expression of CD39. TCR signaling is required for the upregulation of CD39 + on lesional CD8 + T-cells. Pharmacological inhibition of CD39 partly restores cytokine production of CD8 + T-cells in the atherosclerotic lesions. CD8 + T-cells from human lesions display increased expression of CD39 compared to their circulating counterparts.